Introduction to the Special Section on the Intergenerational Transmission of Risk for Substance Use - Kerr, David C. R. (Psychol Addict Behav, 2020)
Six original research papers were submitted to this special section to address questions regarding the intergenerational transmission of risk for cannabis and other substance use. Study teams recruited youth in Iowa, Washington, Oregon, New York, and Arizona in the 1980s–1990s, assessed them into adulthood, and recruited their partners and offspring for another study. All of the studies assessed substance use in two or more generations. Other strengths in this section include the strong representation of fathers, the demographic diversity of the samples as a whole, and the demonstrations of varied statistical and replication approaches. The findings highlight features of parental histories of cannabis use during adolescence that are associated with their children’s risk for cannabis use and factors that explain or weaken intergenerational similarities. Two groups of prevention scholars also offered commentaries on the implications of these studies for prevention and training, and collaboration. It is hoped that the special section will stimulate new hypotheses, replications, and communication among etiological and prevention researchers. Furthermore, the papers highlight that the familial transmission of substance use risk should be taken into account more fully in the design of prevention programs in order to maximize impacts for youth as well as their future offspring.